Summer Multicultural and Interdisciplinary Learning for Engineering (SMILE) in Transportation: Online Professional Development for Future Science Teachers of Culturally and Linguistically Diverse Students - Yoon, Jiyoon; Hyun, Kate; Naz, Farah; Saha, Troyee (Journal of Engineering Education Transformations, 2025)
This study was designed to offer an online professional development opportunity, "Summer Multicultural and Interdisciplinary Learning for Engineering (SMILE) in Transportation," for future elementary STEM teachers and measure its effects on their teaching. As the student population grows more diverse, schools face more significant challenges in delivering practical instructions on "transportation" to the diverse student population, including minority students who speak English as a second language. SMILE in Transportation provided future science teachers with an opportunity to interact with cultural professionals in Transportation who were experts in Transportation, had their cultural backgrounds, and presented transportation systems through their cultures. The cultural professionals in Transportation involved inter-disciplinarily professionals not only on the college campus but also from the communities. SMILE in Transportation was a novel approach to increase the knowledge of future science teachers in Transportation and to develop a unique teaching methodology that incorporates the backgrounds of culturally and linguistically diverse students into teaching engineering of Transportation. The data collected from the pre-and the post-surveys of the participants' science affinities & cultural competency (teaching efficacy, cultural competency, personal interest, & cultural IQ), science knowledge tests, and the qualitative survey at the end of the project were used to improve future teachers' understanding of Transportation and other cultures and their skills in developing culturally- responsive instructions to teach Transportation, as well as to update SMILE workshop for future sessions.